ANALISIS KESULITAN BELAJAR SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL DI SMP NEGERI 2 LANGOWAN - Sudarmadi, Stefanus I Wayan Rafaeliando; Sulangi, Victor R.; Runtu, Patricia V. J (SOSCIED, 2024)
The ability to think mathematically is a basic need in solving various problems in every aspect of human life, including learning mathematics. However, in reality there are several obstacles in learning mathematics, one of which is student difficulties in learning mathematics which has an impact on student learning achievement. From the results of interviews conducted by researchers at SMP Negeri 2 Langowan involving mathematics teachers and several students, it turns out that there are still many students who make mistakes in solving mathematics problems. Students still have difficulty in understanding how to solve mathematical problems (problem solving). This research was conducted in Class VII-A SMP Negeri 2 Langowan, Minahasa Regency with the subjects in this study were students of class VII-A SMP Negeri 2 Langowan 2023/2024. For data collection techniques used in this study include written tests, interviews and documentation. The results showed that the percentage of students who mastered the material of one variable linear equation was 60%, the percentage of students who did not master the material of one variable linear equation was 30% and the percentage of students who did not master the material of one variable linear equation was 10%.